2020
DOI: 10.1002/lio2.462
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment outcome of type 1 thyroplasty using novel titanium medialization laryngoplasty implant combined with arytenoid adduction for unilateral vocal cord paralysis: single‐arm interventional study at a single institution

Abstract: Objective: To evaluate the long-term treatment outcome of type 1 thyroplasty with novel rearrangeable titanium medialization laryngoplasty implant (TMLI) combined with arytenoid adduction (AA) for unilateral vocal cord paralysis (UVFP) in the authors' institution. Methods: A total of 16 Japanese patients with UVFP who received type 1 thyroplasty using TMLI with arytenoid adduction was enrolled in this single-arm, non-randomized interventional study. The results of the auditory perceptual assessment, aerodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Interestingly, the assessment of the Grade of dysphonia at 3 months showed a further decrease of the intraoperative values supporting the earlier observation that the intraoperative environment is not the ideal assessment situation and that further improvements are likely after proper wound healing and speech-language therapy. The overall decrease of the Grade score from 1.4 before surgery to 0.4 at 3 month post-surgery (Δ 1.00 points; p = 0.071), although not significant, is in line with earlier studies that have shown improvements in overall Grade score after MT + AA ranging from 1.0 to 2.5 points [ 8 , 22 24 ]. Finally, the VHI total scores decreased significantly after surgery from a preoperative mean of 71 to 13 at 3 months (Δ 58; p = 0.008) which can be considered as normal [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the assessment of the Grade of dysphonia at 3 months showed a further decrease of the intraoperative values supporting the earlier observation that the intraoperative environment is not the ideal assessment situation and that further improvements are likely after proper wound healing and speech-language therapy. The overall decrease of the Grade score from 1.4 before surgery to 0.4 at 3 month post-surgery (Δ 1.00 points; p = 0.071), although not significant, is in line with earlier studies that have shown improvements in overall Grade score after MT + AA ranging from 1.0 to 2.5 points [ 8 , 22 24 ]. Finally, the VHI total scores decreased significantly after surgery from a preoperative mean of 71 to 13 at 3 months (Δ 58; p = 0.008) which can be considered as normal [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the VHI total scores decreased significantly after surgery from a preoperative mean of 71 to 13 at 3 months (Δ 58; p = 0.008) which can be considered as normal [ 22 ]. Various studies have used the VHI-30 score for voice outcome analysis in MT + AA cohorts reporting mean improvements ranging from 50.3 to 78.8 points [ 5 , 23 , 24 ].We, therefore, conclude that our data show a relevant voice improvement after MT + AA that is comparable with literature. However, in our case intra-operative measurements were not finite and continued to improve post-operatively in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Silicone elastomer, polytetrafluoroethylene paste, pre-molded silastic, calcium hydroxyapatite and titanium are widely used (45). Titanium achieved better outcomes in the current study (46). AA plays a part in UVCP treatment by directly stretching arytenoid cartilage directly.…”
Section: Type I Thyroplasty and Aamentioning
confidence: 63%
“…AA plays a part in UVCP treatment by directly stretching arytenoid cartilage directly. AA is usually adjuvant medialization procedures (46)(47)(48). A novel endoscopic AA with IL was developed as a rapid, minimally invasive solution for UVFP (49).…”
Section: Type I Thyroplasty and Aamentioning
confidence: 99%
“…Besides, for voice rehabilitation other surgical techniques including laryngoplasties and thyreoplasties [12][13][14] have been established. For laryngoplasties which augment the vocal folds, many different synthetic or autologous fillers such as polytetrafluoroethylene (Teflon), calcium hydroxylapatite (CaHa), collagen, hyaluronic acid and fat have been used [15][16][17].…”
Section: Introductionmentioning
confidence: 99%